2020
DOI: 10.1080/14992027.2020.1762126
|View full text |Cite
|
Sign up to set email alerts
|

Music listening and hearing aids: perspectives from audiologists and their patients

Abstract: Objective: Two studies explored hearing-aid user and audiologist experiences of hearing-aid use and fitting for music in the UK. Design and sample: One-hundred-seventy-six hearing-aid users (age range: 21-93 years; mean: 60.56 years) answered a 4-item questionnaire on music listening difficulties and discussions about music in clinic. 99 audiologists (age range: 22-71 years; mean: 39.18 years) answered a 36-item questionnaire on the frequency and type of discussions, training received, and strategies for optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Although these situations are not as prevalent as communicating in noise, users highly motivated to personalize their experience can still benefit from adopting specific listening programs for these situations. The prevalence of the Music program is consistent with previous studies finding that between 30% and 67% of HA users may encounter difficulties with listening to music [ 51 , 52 ] and indicating that the enjoyment of listening to music with HAs could be improved by addressing problems such as distortion, acoustic feedback, insufficient or excessive gain, unbalanced frequency response, and reduced tone quality [ 52 , 53 ]. A listening program dedicated to music has previously been proposed to make music more enjoyable [ 54 ].…”
Section: Discussionsupporting
confidence: 86%
“…Although these situations are not as prevalent as communicating in noise, users highly motivated to personalize their experience can still benefit from adopting specific listening programs for these situations. The prevalence of the Music program is consistent with previous studies finding that between 30% and 67% of HA users may encounter difficulties with listening to music [ 51 , 52 ] and indicating that the enjoyment of listening to music with HAs could be improved by addressing problems such as distortion, acoustic feedback, insufficient or excessive gain, unbalanced frequency response, and reduced tone quality [ 52 , 53 ]. A listening program dedicated to music has previously been proposed to make music more enjoyable [ 54 ].…”
Section: Discussionsupporting
confidence: 86%
“…Such difficulties may subsequently lead to less or non-use of the HA. Conventional HA owners reported difficulties in specific listening situations, e.g., when listening to or performing music ( Greasley et al, 2020 ; Skagerstrand et al, 2014 ; Vaisberg, Martindale, Folkeard, & Benedict, 2019 ) and during telephone conversations ( Gallagher & Woodside, 2018 ; Linssen et al, 2013 ; Skagerstrand et al, 2014 ; Stephens & Meredith, 1991 ). This often resulted in upset and frustration and ultimately affected HA owners’ quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…The HA owners’ attitude was also a common concept in reports of HA owners related to experiences of sub-optimal HA use. Reports reflecting a negative attitude and/or negative emotional state or hesitation towards HA use by owners of conventional HAs were associated with avoidance of or reduced use of HAs ( Chundu et al, 2021 ; Gallagher & Woodside, 2018 ; Greasley et al, 2020 ; Laplante-Lévesque et al, 2012 ; Linssen et al, 2013 ). Hesitation toward user-driven hearing devices was also identified as a challenge to the use of smartphone-connected, app-controlled HAs ( Keidser et al, 2019 ; Ng et al, 2017 ), revealing these owners’ concerns about the outcomes with HAs due to lesser involvement of a hearing care professional (HCP).…”
Section: Resultsmentioning
confidence: 99%
“…Hearing aid users report dissatisfaction with hearing aid processed music (Greasley et al, 2020;Leek et al, 2008;Looi et al, 2019;Madsen & Moore, 2014;Vaisberg et al, 2019), and this may relate to the variable nature of the acoustics of music.Speech is acoustically predictable because it originates from the vocal tract and has well-understood spectral content and levels (Hillenbrand et al, 1995;Olsen, 1998). One study demonstrated similar long-term spectra across 12 languages (Byrne et al, 1994).…”
mentioning
confidence: 99%